Hot topics and frontier evolution in college flipped classrooms based on mapping knowledge domains - Sun, Liyan; Yang, Li; Wang, Xue; Zhu, Junqi; Zhang, Xuesen (Frontiers in Public Health, 2022)
With the outbreak of COVID-19 and the development of online teaching, the online flipping teaching mode has attracted increasing attention. Systematic analysis of the research status and development trend of the flipped classrooms is significant for guiding the improvement of the quality of online flipped teaching. This study used the metrology software CiteSpace to draw a scientific knowledge map of relevant research in the web of science database from 2013 to 2021. It performed visual analysis of research authors, research institutions and countries, keyword clustering, keywords co-occurrence and keyword time zone distribution. The results showed that: (1) The flipped classrooms research has attracted increasing attention from the social and educational circles, however, the relationship between relevant research authors, institutions and countries is not close enough, and there is little cooperation. We need to strengthen cooperation further and realize the sharing of high-quality resources; (2) Based on keyword co-occurrence cluster analysis, this study identified three hot topics, namely, preparation before class, classroom activities and consolidation after class; (3) According to the keyword time zone map, this study divided three frontier evolution trends: explore period, adaptation period, and growth period; (4) Finally, with the spread of novel coronavirus, it is suggested to promote the online flipped classroom teaching mode, and put forward reasonable suggestions from the perspective of teachers, students and researchers, and look forward to the future digital development direction of the flipped classroom.